Pengawasan Dinas Perhubungan Terhadap Kelayakan Kendaraan Angkutan Jalan Di Kabupaten Tangerang Berdasarkan Peraturan Daerah Kabupaten Tangerang Nomor 4 Tahun 2018 Tentang Penyelenggaraan Perhubungan - Siti Sulaemah Cunayah; H. E. Rakhmat Jazuli; Ahmad Lanang Citrawan (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the issue of the effectiveness of the Transportation Agency’s oversight of the roadworthiness of road transport vehicles in Tangerang Regency based on Tangerang Regency Regional Regulation No. 4 of 2018, which in practice still reveals a gap between legal norms and implementation. The study employs an empirical method with a socio-legal approach through data collection via interviews, observations, and documentary analysis, and is qualitatively analyzed using legal interpretive techniques. The findings indicate that supervision remains suboptimal due to institutional capacity constraints, low compliance among business operators, as well as weak enforcement of sanctions and inter-agency coordination. Normatively, regulations have comprehensively established vehicle fitness standards; however, their implementation has not fully met the objectives of safety and legal protection. The socio-legal approach reveals that legal culture and the quality of public services also influence the effectiveness of supervision. This study contributes to the development of an integrative analysis between legal norms and empirical practices in transportation governance.